Validation of sheath blight resistance in Tetep derived Basmati and parental lines of rice hybrid - and U.D. SINGH1, R.T.P. PANDIAN1, P. SHARMA1, V.K. SINGH2 A. SINGH2, R.K. ELLUR2, A.K. SINGH2 (Indian Phytopathology, 2012)
Sheath blight is one of the destructive diseases of rice, caused by the fungus Rhizoctonia solani Kuhn (Teleomorph: Thanatephorus cucumeris (Frank) Donk.). The pathogen is polyphagous in nature and the host plant resistance is governed by polygenes. In a backcross breeding program at IARI, New Delhi, in order to incorporate blast resistance into the background of Basmati rice genotype (Pusa1460) and parental lines of superfine grain aromatic rice hybrid Pusa RH10 (PRR78; restorer line and Pusa6B; maintainer line), Tetep was used as donor for the blast resistance gene Pi54, thereby developed 186 blast resistance advanced backcross inbred lines. Recently, ‘Tetep’ was reported to carry 12 QTLs governing sheath blight resistance. Parental screening for the sheath blight resistance using a highly virulent isolate Kapurtala depicted that the donor parent Tetep was highly resistant and the recurrent parents were moderately susceptible (PRR78) to susceptible (Pusa1460 and Pusa6B). Further, evaluation of 186 advanced backcross inbred lines for sheath blight resistance revealed that nine Pusa6B derived inbred lines were resistant; eleven Pusa1460 derived inbred lines and twelve PRR78 derived lines were moderately resistant to sheath blight. The varying quantum of resistance depicted by the field screening implies that, varying number of QTLs present in the residual donor segments of the ABLs. These identified resistant lines in the background of Pusa6B can be used as maintainer line for the development of Basmati hybrids with blast and sheath blight resistance.